Two-level inverter and three-level neutral point diode clamped inverter for traction applications: a comparative analysis study - Asmaa A. Abdelsalam; Mohamed Adel Esmaeel; Salama Abo Zaid (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents an analytical comparison between two-level inverter and three-level neutral point diode clamped inverters for electric vehicle traction purposes. The main objective of the research is to declare the main differences in the performance of the two inverter schemes in terms of the switching and conduction losses over an entire domain of the modulation index and the phase angle distribution, steady-state operation, transient operation at a wide range of speed variation, and the total harmonic distortion THD% of the line voltage output waveform. It also declares the analysis of the three-level neutral point diode clamped inverter (NPCI) obstacle and the unbalance of the DC-link capacitor voltages. The introduced scheme presents an Induction Motor (IM) drive for electric vehicle (EV) applications. Considering the dynamic operation of the EV, the speed of the three-phase induction motor is controlled using a scalar V/Hz control for the full range of the IM power factor (PF). A comprehensive MATLAB/Simulink model for the proposed scheme is established.